2016
DOI: 10.1186/s12860-016-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

IL-27 inhibits the TGF-β1-induced epithelial-mesenchymal transition in alveolar epithelial cells

Abstract: AbstractsBackgroundIL-27 is a multifunctional cytokine that has both pro-inflammatory and anti-inflammatory functions. Although IL-27 has been shown to potently inhibit lung fibrosis, the detailed mechanism of IL-27 in this process is poorly understood. Epithelial–mesenchymal transition (EMT) is one of the key mechanisms involved in pulmonary fibrosis. We assessed the effects of IL-27 on TGF-β1-induced EMT in alveolar epithelial cells.MethodsA549 cells (a human AEC cell line) were incubated with TGF-β1, IL-27,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
5
25
0
Order By: Relevance
“…the results showed that IL-27 treatment did not exert adverse toxic effects on non-cancerous breast cells, 184b5 but managed to inhibit more than 50% of MCF-7 and MDA-MB-231 breast cancer cell growth after 48-and 72-h treatments, respectively. this finding is in line with Dong et al (2016) in which IL-27 was shown to be able to exert significant cytotoxicity to A549 lung carcinoma cells after 48 h of treatment. Besides, the cytotoxicity of IL-27 in both cancer cell lines also increased in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 91%
“…the results showed that IL-27 treatment did not exert adverse toxic effects on non-cancerous breast cells, 184b5 but managed to inhibit more than 50% of MCF-7 and MDA-MB-231 breast cancer cell growth after 48-and 72-h treatments, respectively. this finding is in line with Dong et al (2016) in which IL-27 was shown to be able to exert significant cytotoxicity to A549 lung carcinoma cells after 48 h of treatment. Besides, the cytotoxicity of IL-27 in both cancer cell lines also increased in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 91%
“…The data in the present study suggests also a role of TSP‐1 in TGFβ signaling in response to MWCNT in alveolar cells. Although, fibroblasts are central to fibrosis, other lung cells including alveolar epithelial cells are emerging contributors to fibrosis development . Treatment of alveolar epithelial cells treated with TGFβ induces the expression of EMT markers, vimentin and α‐smooth muscle actin, or collagen type I (α‐SMA) .…”
Section: Discussionmentioning
confidence: 99%
“…Although, fibroblasts are central to fibrosis, other lung cells including alveolar epithelial cells are emerging contributors to fibrosis development . Treatment of alveolar epithelial cells treated with TGFβ induces the expression of EMT markers, vimentin and α‐smooth muscle actin, or collagen type I (α‐SMA) . Several other studies indicate EMT role in lung fibrosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GO term analysis showed that binding (GO: 0005488) and catalytic activity (GO:0003824) are two most widely distributed groups among all mutated genes ( Figure 1A), and the two most enriched pathways are 1) Immune response B cell antigen receptor (BCR) pathway, and 2) development positive regulation of STK3/4 (Hippo) pathway and negative regulation of YAP/TAZ function. Table 1: Selected mutated genes from 10 enriched pathways in Figure 1B [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Mutations Acquired In Castration Resistant Cell Linesmentioning
confidence: 99%